2020
DOI: 10.1007/s10754-020-09278-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pay-for-performance on prescription of hypertension drugs among public and private primary care providers in Sweden

Abstract: This study exploits policy reforms in Swedish primary care to examine the effect of pay-for-performance (P4P) on compliance with hypertension drug guidelines among public and private health care providers. Using provider-level outcome data for 2005–2013 from the Swedish Prescription Register, providers in regions using P4P were compared to providers in other regions in a difference-in-differences analysis. The results indicate that P4P improved guideline compliance regarding prescription of angiotensin convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(53 reference statements)
0
3
2
Order By: Relevance
“…Contrary to the findings by Maun et al (2015), public PCCs also adhered better to prescription guidelines regarding harmful drugs for elderly in the studied region. This result also differs from findings by Ellegård (2020) who found that private PCCs adhered better to prescription guidelines compared to public PCCs in Sweden. However, compliance with guidelines was linked to financial incentives in pay-for-performance schemes in the study by Ellegård (2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the findings by Maun et al (2015), public PCCs also adhered better to prescription guidelines regarding harmful drugs for elderly in the studied region. This result also differs from findings by Ellegård (2020) who found that private PCCs adhered better to prescription guidelines compared to public PCCs in Sweden. However, compliance with guidelines was linked to financial incentives in pay-for-performance schemes in the study by Ellegård (2020).…”
Section: Discussioncontrasting
confidence: 99%
“…This result also differs from findings by Ellegård (2020) who found that private PCCs adhered better to prescription guidelines compared to public PCCs in Sweden. However, compliance with guidelines was linked to financial incentives in pay-for-performance schemes in the study by Ellegård (2020). One interpretation, in line with theoretical assumptions about differences across owner types (Kornai et al, 2003;Frey et al, 2013), is that monetary incentives are stronger for private (for-profit) than public providers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Granlund [ 15 ] found that private doctors were more likely to disallow generic substitution. More recently, Ellegård [ 16 ] studied how pay-for-performance incentives affected primary care providers’ compliance with hypertension drug guidelines and found that private providers reacted more strongly to the economic incentives. To our knowledge, there are no studies to date addressing the impact of ownership of healthcare centres on the prescription of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not find any indications of gaming by prescribing more antibiotics overall to increase the share of narrow-spectrum antibiotics. Furthermore, Ellegård [ 35 ] examined the effect of P4P on compliance with hypertension drug guidelines among public and private healthcare providers. The results showed that P4P incentives had a significant effect on guideline compliance and that the effect was most noticeable for private providers, indicating that private providers are more responsive towards financial incentives.…”
Section: Resultsmentioning
confidence: 99%